2017
DOI: 10.1080/09205063.2017.1367635
|View full text |Cite
|
Sign up to set email alerts
|

Small diameter vascular graft with fibroblast cells and electrospun poly (L-lactide-co-ε-caprolactone) scaffolds: Cell Matrix Engineering

Abstract: Electrospun scaffolds have been widely used in tissue engineering due to their similar structure to native extracellular matrices (ECM). However, one of the obstacles limiting the application of electrospun scaffolds for tissue engineering is the nano-sized pores, which inhibit cell infiltration into the scaffolds. To overcome this limitation, we approached to make layers which are consisted of cells onto the electrospun sheet and then tubular structure was constructed by rolling. We called this as 'Cell Matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In another study, Jang et al electrospun small diameter vascular graft comprising poly( l ‐lactide‐ co ‐ε‐caprolactone). In vitro experiments showed that the fabricated vascular graft exhibited better fibroblast cell attachment and proliferation . Hence, these literature showed that the fibroblast cells play a vital role in remodeling the damaged cardiac tissue.…”
Section: Resultsmentioning
confidence: 96%
“…In another study, Jang et al electrospun small diameter vascular graft comprising poly( l ‐lactide‐ co ‐ε‐caprolactone). In vitro experiments showed that the fabricated vascular graft exhibited better fibroblast cell attachment and proliferation . Hence, these literature showed that the fibroblast cells play a vital role in remodeling the damaged cardiac tissue.…”
Section: Resultsmentioning
confidence: 96%
“…Hence, our fabricated composites with a smaller fibre diameter than PU might have favoured the smoother surfaces. It has been reported that fibroblast cell adhesion favours the growth of cardiac tissue (Saporito et al, 2018; Jang et al, 2018). It has been reported that the smooth surface membranes displayed enhanced proliferation rates of fibroblast cells (Huag et al, 2009).…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Hence, the fibroblast cells play a key role in repairing the damaged cardiac tissue. 52,53 Kim et al investigated the effect of the fiber diameter on the surface roughness of electrospun poly(ε-caprolactone) scaffolds. It had been found that a scaffold with a smaller fiber diameter showed a smoother morphology and became rougher when the diameter became larger.…”
Section: Afm Analysismentioning
confidence: 99%